Rendang Lokan as A Culinary Tourism Attraction in Pesisir Selatan - Nadra, Abdiani Khairat; Nora, Efmilia (Institut Pariwisata dan Bisnis Internasional, 2020)
The tourism trend in which culinary tourism is one of the favorite tourist attractions that is favored provides opportunities for areas that have distinctive culinary delights, Pesisir Selatan is one of the areas that has traditional culinary specialties which if developed will become one of the tourist attractions. This study aims to see whether the culinary specialties of Pesisir Selatan Rendang Lokan has the potential to be developed as a tourist attraction. This research is descriptive with a qualitative approach, using Damanik and Weber's theory of uniqueness, originality, authenticity and diversity and is supported by Yoeti's theory of tourist attraction, namely having something to see, something to do and something to buy. Data collection was carried out by interview and observation. The results showed that Rendang Lokan has the potential to be developed as a tourist attraction. This can be seen from the uniqueness of its taste, its originality and consistency in the use of the same ingredients that has not changed since the past, its authenticity in the traditional manufacturing process, and its diversity on its flavors. As a tourist attraction, Rendang Lokan also meets the criteria of